Enhancing quality management in Indonesia's flexible packaging industry: A six sigma approach to defect reduction and cost savings - Keanoubie, Muhammad; Kusumastuti, Ratih Dyah (Journal of Entrepreneurial Economics, 2025)
Background: The flexible packaging industry is experiencing significant growth, requiring companies to improve efficiency by reducing defects and minimizing the cost of poor quality (COPQ). Effective quality control is crucial to maintaining competitiveness and reducing waste. This study focuses on assessing and improving quality control in an Indonesian flexible packaging company, XYZ, using the Six Sigma methodology. Methods: The research adopts the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) approach to identify defects and propose solutions. Data collection includes statistical analysis, historical records, and interviews with company sources. The study specifically examines defects in the printing process, which accounts for 79% of total defects based on the 80/20 principle. The Failure Mode and Effects Analysis (FMEA) model is applied to identify root causes and develop recommendations for improvement. Findings: The study identifies multiple factors contributing to printing defects, such as register shifting, film scratching, color inconsistencies, ink transfer issues, and ink spots. Operator performance and machine-related issues are found to be the dominant causes of defects. Implementing the recommended quality control improvements can potentially reduce defect-related costs by 48%, translating to estimated cost savings of IDR 114,734,847 during the study period. Conclusion: This research confirms the effectiveness of Six Sigma in reducing defects and improving production efficiency in the flexible packaging industry. However, limitations include restricted access to ERP data, reliance on interviews and historical records, and the inability to evaluate the implementation of control measures. Novelty/Originality of this article: This study contributes to the literature by applying Six Sigma in a flexible packaging industry context in Indonesia, demonstrating its potential for substantial cost savings. Unlike previous studies, it emphasizes the human factor in quality control and suggests a systematic approach to defect reduction.